2022
DOI: 10.1093/ofid/ofac186
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Casirivimab-Imdevimab Monoclonal Antibody Treatment Among High-Risk Patients With Severe Acute Respiratory Syndrome Coronavirus 2 B.1.617.2 (Delta Variant) Infection

Abstract: BACKGROUND Real-world data on the effectiveness of neutralizing Casirivimab-Imdevimab monoclonal antibody (Cas-Imd mAb) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among high-risk patients may inform the response to future SARS-CoV-2 variants. METHODS This study covers an observational retrospective data analysis in Banner Health Care System sites, mainly in Arizona. During the study period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…REGEN-COV is a combination of two fully human non-competing mAbs, casirivimab (REGN10933) and imdevimab (REGN10987), both of which target the ACE2-binding interface of SARS-CoV-2 RBD and function to block RBD/ACE2 interaction 16 . In vitro experiments demonstrated that the combination could neutralise mutants selected 17 ( https://www.covid19treatmentguidelines.nih.gov/therapies/anti-sars-cov-2-antibody-products/anti-sars-cov-2-monoclonal-antibodies/ ) using single components 18 , 19 . A previous report also suggested that treatment with REGEN-COV would be unlikely to lead to the emergence of escape mutants in both preclinical and human studies 20 .…”
Section: Introductionmentioning
confidence: 99%
“…REGEN-COV is a combination of two fully human non-competing mAbs, casirivimab (REGN10933) and imdevimab (REGN10987), both of which target the ACE2-binding interface of SARS-CoV-2 RBD and function to block RBD/ACE2 interaction 16 . In vitro experiments demonstrated that the combination could neutralise mutants selected 17 ( https://www.covid19treatmentguidelines.nih.gov/therapies/anti-sars-cov-2-antibody-products/anti-sars-cov-2-monoclonal-antibodies/ ) using single components 18 , 19 . A previous report also suggested that treatment with REGEN-COV would be unlikely to lead to the emergence of escape mutants in both preclinical and human studies 20 .…”
Section: Introductionmentioning
confidence: 99%
“…REGEN-COV is a cocktail of two fully human non-competing nmAbs, casirivimab (REGN10933) and imdevimab (REGN10987), both of which target the ACE2-binding interface of SARS-CoV-2 RBD and function to block RBD/ACE2 interaction (Hansen et al, 2020). In vitro experiments demonstrated that the cocktail could neutralise mutants selected (Al-Obaidi et al, 2022) (https://www.covid19treatmentguidelines.nih.gov/therapies/anti-sars-cov-2-antibody-products/anti-sars-cov-2-monoclonal-antibodies/) using single components (Baum et al, 2020; Liu et al, 2021). A previous report also suggested that treatment with REGEN-COV would not lead to the emergence of escape mutants in both preclinical and human studies (Copin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, it effectively declined ED visits in COVID-19 patients. Studies23,[40][41][42][43][44][45] demonstrate that patients treated with antiviral agents were significantly less likely to be admitted to ICU and visit the ED compared with untreated patients.…”
mentioning
confidence: 99%